Bioethanol yield produced from moringa oleifera seeds husk - Siti Zulaikha, Kemat (2016)
This paper presents ethanol production from lignocellulosic materials which is Moringa oleifera seeds husk through Simultaneous Saccharification and Fermentation (SSF) process by using Saccharomyces cerevisiae. This paper investigates the production of bioethanol from Moringa oleifera seeds husk and the most affecting parameters that affect the bioethanol yield. The husk was pre‒treated, hydrolyzed using alkaline technique and fermented using Simultaneous Saccharification and Fermentation (SSF) technique using Saccharomyces cerevisiae yeast. Batch fermentation was performed with different yeast dosage, pH value and fermentation time. The pH value varies between 4.5, 5.0 and 5.5 while the yeast dosage was manipulated at 1 g/L, 3 g/L and 5 g/L. For fermentation time, the sample was taken for every 3 hours within 12 hours fermentation time which are 3, 6, 9 and 12 hours, respectively. The temperature of fermentation process in stackable incubator shaker was kept constant at 32ºC. The samples are then filtered using a 0.20 μm nylon syringe filter. The yield of bioethanol produced was analysed using High Performance Liquid Chromatography (HPLC).